Kaj imajo skupnega Andy Warhol, pekorino in vasabi? - Kamin, Tanja (Družboslovne razprave, 2012)
The authors present an analysis of food practices based on the research project "Media consumption, class and cultural stratification". A cluster analysis of data obtained from a random sample of the adult population in Ljubljana and Maribor, the two biggest cities in Slovenia, revealed four food cultures: Aspiring traditionalists (27% of the sample), Struggling traditionalists (32%), Health conscious and socially responsible hedonists (29%) and Traditionalists, adapted to urban trends (12%). The findings support previous research which recognises significant associations between food practices, socio-demographic factors (particularly education), values and cultural consumption. The data show that food practices in Ljubljana and Maribor are still primarily traditionalistic, as are several other practices of everyday life.
Keywords: Food habits; Prehranjevalne navade; Lifestyles; Življenjski stili; Zdravje; Health; Slovenia; Slovenija; prehranjevanje; sociologija prehrane